Pendidikan Vokasional Agribisnis untuk Mengoptimalkan Pemanfaatan Sumber Daya Pertanian di Wilayah Yosomulyo - Nadhella; Astri Shabrina; Iqbal Choirul Fadil (Institut Agama Islam Ma’arif NU (IAIMNU) Metro Lampung, 2023)
Abstract The agricultural community in Yosomulyo possesses significant natural resource potential, yet faces challenges in optimizing its utilization due to limited knowledge and skills in modern agribusiness practices. This community service program aimed to enhance farmers' vocational competencies through targeted training, enabling them to maximize agricultural productivity and market opportunities. Employing a participatory action research (PAR) approach and the experiential learning theory, the intervention included hands-on workshops on sustainable farming techniques, product diversification, and digital marketing. Results demonstrated a 65% increase in participants' understanding of agribusiness management, with 12 local farmers adopting new cultivation methods and 5 establishing online sales platforms. The program also fostered the formation of a farmer group committed to applying the acquired skills collectively. These findings underscore the effectiveness of vocational education in empowering rural communities to leverage their agricultural resources more efficiently.